A barium titanate ceramic piezoelectric film and preparation method thereof

By controlling grain boundary density in barium titanate ceramic piezoelectric films through specific raw material ratios and electrospinning, the preparation process is simplified and piezoelectric performance is enhanced, eliminating the need for polarization.

CN118851745BActive Publication Date: 2024-12-20SICHUAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340939.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-20
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The preparation process of ceramic piezoelectric films is complicated due to the need for polarization after calcination, which affects the efficiency and complexity of the process.

Method used

A method for preparing barium titanate ceramic piezoelectric films by controlling the grain boundary density through specific raw material ratios and electrospinning, eliminating the need for polarization treatment.

Benefits of technology

The method simplifies the preparation process and enhances piezoelectric catalytic performance by directly achieving piezoelectric activity without polarization, improving efficiency and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118851745B_ABST
    Figure CN118851745B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramic materials, and in particular to a barium titanate ceramic piezoelectric film and a preparation method thereof, comprising the following steps: obtaining a barium titanate precursor solution, wherein the mass percentage of the barium source in the raw material of the barium titanate precursor solution is 20% to 25%, and the stoichiometric molar ratio of Ba to Ti is 1:1; preparing the barium titanate precursor solution into a barium titanate precursor film; and calcining the barium titanate precursor film to obtain a barium titanate ceramic piezoelectric film. The present invention selects raw materials containing a specific mass ratio of titanium source and barium source to prepare a barium titanate ceramic piezoelectric film, thereby improving the grain boundary density of the barium titanate ceramic piezoelectric film at the microscopic level, so that the barium titanate ceramic piezoelectric film obtained after calcination directly has piezoelectric catalytic performance without the need for further polarization treatment, thereby simplifying the preparation process of the barium titanate ceramic piezoelectric film and improving the preparation efficiency of the ceramic piezoelectric film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a barium titanate ceramic piezoelectric film and a preparation method thereof. Background Art

[0002] Ceramic piezoelectric film is a special ceramic material film with piezoelectric effect, which can convert mechanical energy into electrical energy or vice versa. In the preparation process of ceramic piezoelectric film, polarization is a key process. Polarization refers to the process in which the charge center inside the piezoelectric ceramic film is relatively displaced under a certain electric field, resulting in the appearance of bound charges of opposite signs on the surfaces of both ends of the material. In the process of realizing the present invention, the applicant found that the preparation process of existing ceramic piezoelectric films is relatively complicated. Summary of the invention

[0003] The purpose of the present invention is to provide a barium titanate ceramic piezoelectric film and a preparation method thereof to solve the above technical problems existing in the prior art, which mainly include the following two aspects:

[0004] The first aspect of the present invention provides a method for preparing a barium titanate ceramic piezoelectric film, comprising the following steps:

[0005] Step S100, obtaining a barium titanate precursor solution, wherein the raw materials of the barium titanate precursor solution include a barium source and a titanium source, the mass percentage of the barium source in the raw materials is 20% to 25%, and the stoichiometric molar ratio of the titanium source and the barium source in the raw materials is 1:1;

[0006] Step S200, preparing a barium titanate precursor film from a barium titanate precursor solution;

[0007] Step S300, calcining the barium titanate precursor film to obtain a barium titanate ceramic piezoelectric film.

[0008] Furthermore, the barium source is at least one of barium titanate, barium acetate, barium sulfate, barium nitrate, barium chloride, barium hydroxide and barium oxide.

[0009] Furthermore, the titanium source is at least one of titanium dioxide colloid, titanium trichloride, titanium tetrachloride, titanyl sulfate, titanyl acetylacetonate, isopropyl titanate, tetrabutyl titanate and tetraethyl titanate.

[0010] Furthermore, the raw materials of the barium titanate precursor solution also include a thickening and crosslinking agent;

[0011] And / or, the raw materials of the barium titanate precursor solution further include a solvent, and the solvent is any one of an acetic acid-ethanol-deionized water solvent system, an acetic acid-DMF-deionized water solvent system, and an acetic acid-DMF-acetylacetone solvent system.

[0012] Furthermore, in step S200, the barium titanate precursor solution is made into a barium titanate precursor film by electrostatic spinning.

[0013] Furthermore, during the electrospinning process, the barium titanate precursor sol is electrospun onto a spinning template having a topological structure.

[0014] The positive voltage for controlling electrospinning was +16 kV, and the negative voltage was -4 kV;

[0015] and / or, the spinning temperature is controlled at 25±5°C and the humidity is controlled at 40%±5%;

[0016] And / or, the spinning thickness is controlled to be 3 μm~10 μm.

[0017] Furthermore, during the electrospinning process, the barium titanate precursor sol is electrospun onto a common receiver.

[0018] Furthermore, in step S300, the calcination temperature is controlled to be 650°C-900°C, and the calcination time is 8 hours.

[0019] Furthermore, during calcination, the temperature was increased to 650°C~900°C at a heating rate of 2°C / min and maintained in the temperature range for calcination for 8 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a barium titanate ceramic piezoelectric film.

[0020] A second aspect of the present invention provides a barium titanate ceramic piezoelectric film prepared by the above-mentioned preparation method.

[0021] Compared with the prior art, the present invention has at least the following technical effects:

[0022] The present invention prepares barium titanate ceramic piezoelectric film by selecting raw materials containing a specific mass ratio of a titanium source and a barium source, thereby improving the grain boundary density of the barium titanate ceramic piezoelectric film at the microscopic level, so that the barium titanate ceramic piezoelectric film obtained after calcination directly has piezoelectric catalytic performance without the need for further polarization treatment, thereby simplifying the preparation process of the barium titanate ceramic piezoelectric film and improving the preparation efficiency of the ceramic piezoelectric film. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 It is a flow chart of the method for preparing the barium titanate ceramic piezoelectric film of the present invention;

[0025] Figure 2 is a scanning electron microscope image of the film obtained in Example 1;

[0026] Figure 3 is a scanning electron microscope image of the film obtained in Comparative Example 1;

[0027] Figure 4 is a scanning electron microscope image of the film obtained in Example 2;

[0028] Figure 5 is a scanning electron microscope image of the film obtained in Comparative Example 2;

[0029] Figure 6 is a scanning electron microscope image of the film obtained in Example 3;

[0030] Figure 7 is a scanning electron microscope image of the film obtained in Comparative Example 3;

[0031] Figure 8 It is the X-ray diffraction spectra of the films prepared in Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0032] The following description provides many different embodiments or examples for implementing different features of the present invention. The components and arrangements described in the following specific examples are only used to concisely express the present invention, which are only examples and are not intended to limit the present invention.

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention.

[0034] In the prior art, materials for piezoelectric films usually include piezoelectric organic polymers, piezoelectric ceramics, or composite materials composed of piezoelectric organic polymers and piezoelectric ceramics. Among them, piezoelectric organic polymers are flexible and processable, such as polyvinylidene fluoride (PVDF) and polyamide 11 (PA-11), but their piezoelectric coefficients, electron mobility, and electromechanical coupling constants are low. Composite materials composed of piezoelectric organic polymers and piezoelectric ceramics are an effective way to improve piezoelectric and dielectric properties, but poor dispersibility between the two components, interface pore defects, and cracks will limit piezoelectric properties. In comparison, pure phase piezoelectric ceramics have the best piezoelectric properties. However, in the preparation process of pure phase piezoelectric ceramics, such as the preparation method and film of barium titanate ceramic film disclosed in Chinese Patent Publication No. CN117466640A, after the barium titanate precursor film is calcined to obtain a barium titanate ceramic film, the barium titanate ceramic film needs to be polarized to allow the material to exhibit piezoelectric activity, that is, polarization is a necessary preparation process for piezoelectric materials at present. The applicant discovered in the process of realizing the present invention that the grain boundary density affects the piezoelectric catalytic performance of the barium titanate ceramic piezoelectric film. The present application provides a barium titanate ceramic piezoelectric film and a preparation method thereof. The piezoelectric catalytic performance of the barium titanate ceramic piezoelectric film is presented in advance by changing the grain boundary density during the preparation process. In this way, the polarization process is omitted during the preparation process, the preparation process of the ceramic piezoelectric film is simplified, and the preparation efficiency of the ceramic piezoelectric film is improved. The details are as follows:

[0035] A barium titanate ceramic piezoelectric film, such as Figure 1 As shown, it is prepared by a method comprising the following steps:

[0036] Step S100, obtaining a barium titanate precursor solution, wherein the raw materials of the barium titanate precursor solution include a barium source and a titanium source, the mass percentage of the barium source in the raw materials is 20% to 25%, and the stoichiometric molar ratio of the titanium source and the barium source in the raw materials is 1:1;

[0037] Step S200, preparing a barium titanate precursor film from a barium titanate precursor solution;

[0038] Step S300, calcining the barium titanate precursor film to obtain a barium titanate ceramic piezoelectric film.

[0039] Barium titanate ceramic piezoelectric film is prepared by selecting raw materials containing a specific mass ratio of titanium source and barium source, so as to improve the grain boundary density of the barium titanate ceramic piezoelectric film at the microscopic level, so that the barium titanate ceramic piezoelectric film obtained after calcination directly has piezoelectric catalytic properties without the need for further polarization treatment, thereby simplifying the preparation process of barium titanate ceramic piezoelectric film and improving the preparation efficiency of ceramic piezoelectric film.

[0040] Specifically, the barium source is at least one of barium titanate, barium acetate, barium sulfate, barium nitrate, barium chloride, barium hydroxide and barium oxide.

[0041] Specifically, the titanium source is at least one of titanium dioxide colloid, titanium trichloride, titanium tetrachloride, titanyl sulfate, titanyl acetylacetonate, isopropyl titanate, tetrabutyl titanate and tetraethyl titanate.

[0042] Specifically, the raw materials of the barium titanate precursor solution also include a thickening crosslinking agent; the thickening crosslinking agent is at least one of vinyl alcohol, polyvinylidene fluoride, polyethylene oxide, polyvinyl acetate, polyvinyl butyral and polyvinyl pyrrolidone, the preferred thickening crosslinking agent is polyvinyl pyrrolidone, and the mass percentage of the thickening crosslinking agent in the raw materials is 5wt%.

[0043] And / or, the raw materials of the barium titanate precursor solution also include a solvent, and the solvent is any one of an acetic acid-ethanol-deionized water solvent system, an acetic acid-DMF-deionized water solvent system, and an acetic acid-DMF-acetylacetone system; preferably, the solvent is acetic acid, ethanol, and deionized water in a mass ratio of 4:5:1.

[0044] Specifically, in step S200, a barium titanate precursor solution is made into a barium titanate precursor film by electrostatic spinning.

[0045] Specifically, during the electrospinning process, the barium titanate precursor sol is electrospun onto a spinning template with a topological structure, and the positive voltage of the electrospinning is controlled to be +16kV and the negative voltage is controlled to be -4kV; the spinning temperature is controlled to be 25±5°C and the humidity is controlled to be 40%±5%; and the spinning thickness is controlled to be 3μm~10μm.

[0046] In some implementations, during the electrospinning process, the barium titanate precursor sol can be electrospun onto a common receiver.

[0047] Specifically, the calcination temperature is controlled to be 650° C.-900° C., and the calcination time is 8 h.

[0048] Specifically, during calcination, the temperature is increased to 600°C-900°C at a heating rate of 2°C / min and maintained in this temperature range for calcination for 8 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a barium titanate ceramic piezoelectric film.

[0049] Example 1

[0050] A barium titanate ceramic piezoelectric film is prepared by a method comprising the following steps:

[0051] Step S100, dissolving 5% polyvinyl pyrrolidone (PVP) by mass in a mixed solution of ethanol, water and acetic acid in a mass ratio of 5:1:4, then adding 20% ​​barium acetate by mass and tetrabutyl titanate (TBT) in an amount maintaining a stoichiometric molar ratio of Ba to Ti of 1:1 to the mixed solution, stirring until the solution is clear, and then ultrasonicating the solution at a power of 50 W and a frequency of 40 kHz for 30 minutes to obtain a barium titanate precursor solution;

[0052] Step S200, electrospinning the barium titanate precursor solution simultaneously using multiple nozzles, using a propulsion speed of 0.75 mL / h, setting a positive voltage of 16 kV, a negative voltage of -3 kV, and a distance between the spinning needle and the receiver of 16 cm. The spinning temperature is controlled to be 25±5°C, and the humidity is 40%±5%. The spun film is dried in an oven at 60°C for more than 2 hours to obtain a barium titanate precursor film.

[0053] Step S300, heating the barium titanate precursor film to 800°C in a tube furnace at a heating rate of 2°C / min, and continuously calcining for 8 hours, and then cooling it to room temperature at a cooling rate of 5°C / min to obtain a barium titanate ceramic piezoelectric film.

[0054] Example 2

[0055] A barium titanate ceramic piezoelectric film, different from Example 1, in step S300, the barium titanate precursor film is heated to 650°C in a tubular furnace at a heating rate of 2°C / min, and calcined for 8 hours, and then cooled to room temperature at a cooling rate of 5°C / min.

[0056] Example 3

[0057] A barium titanate ceramic piezoelectric film, different from Example 1, in step S300, the barium titanate precursor film is heated to 900°C in a tubular furnace at a heating rate of 2°C / min, and calcined for 8 hours, and then cooled to room temperature at a cooling rate of 5°C / min.

[0058] Comparative Example 1

[0059] A barium titanate ceramic piezoelectric film is different from Example 1. In step S100, 9% by mass of barium acetate and tetrabutyl titanate (TBT) in an amount maintaining a stoichiometric molar ratio of Ba to Ti of 1:1 are added to a mixed solution.

[0060] Comparative Example 2

[0061] A barium titanate ceramic piezoelectric film is different from Example 2. In step S100, 9% by mass of barium acetate and tetrabutyl titanate (TBT) in an amount maintaining a stoichiometric molar ratio of Ba to Ti of 1:1 are added to the mixed solution.

[0062] Comparative Example 3

[0063] A barium titanate ceramic piezoelectric film is different from Example 4. In step S100, 9% by mass of barium acetate and tetrabutyl titanate (TBT) in an amount maintaining a stoichiometric molar ratio of Ba to Ti of 1:1 are added to the mixed solution.

[0064] Comparative Example 4

[0065] A barium titanate ceramic piezoelectric film, different from comparative example 3, the product obtained in comparative example 3 is pressed into a dense film under a pressure of 20 MPa, and then an axial high-voltage electric field is applied to both sides of the film using two copper plate electrodes, and the electric field size is 2 kV mm -1 The entire device was placed in an oven and polarized at 120 °C for 2 h and then at 100 °C for 3 h to ensure complete polarization. The polarization treatment was carried out under this condition.

[0066] The thin films obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were collected for grain boundary density detection and catalytic rate detection. Figure 2~Figure 7 As shown, Figure 2 This is a scanning electron microscope image of the film obtained in Example 1. Figure 3 This is a scanning electron microscope image of the film obtained in Comparative Example 1. Figure 4 This is a scanning electron microscope image of the film obtained in Example 2. Figure 5 This is a scanning electron microscope image of the film obtained in Comparative Example 2. Figure 6 This is a scanning electron microscope image of the film obtained in Example 3. Figure 7 This is a scanning electron microscope image of the film obtained in Comparative Example 3 (the polarization treatment did not change the microscopic morphology of the material, and the microscopic morphology of the film obtained in Comparative Example 4 was the same as that of the film obtained in Comparative Example 3); Figure 8 The X-ray diffraction spectra of the films obtained in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in FIG. 1 . The test conditions for the grain boundary density detection are to perform scanning electron microscopy (SEM) and X-ray diffraction spectrum (XRD) tests on the samples at room temperature and pressure, to count the wire diameters of the samples and calculate the grain sizes, and to obtain the grain boundary density data. The test conditions for the catalytic rate detection are to ultrasonically degrade a methylene blue solution with a concentration of 2 mg / L for 2 h at an ultrasonic frequency of 40 kHz and a power of 90 W, to sample and test the absorbance at intervals, and to calculate the piezoelectric catalytic rate constant. The test results are shown in Table 1.

[0067] Table 1 Photoelectrocatalytic performance of the films obtained in Examples 1 to 3 and Comparative Examples 1 to 3

[0068] .

[0069] It can be seen from Table 1 that the barium titanate ceramic piezoelectric film is prepared by selecting raw materials containing a specific mass ratio of a titanium source and a barium source, so that the grain boundary density of the barium titanate ceramic piezoelectric film is improved at the microscopic level, and the piezoelectric catalytic performance of the barium titanate ceramic piezoelectric film is enhanced by utilizing the increased grain boundary density, so that the barium titanate ceramic piezoelectric film obtained after calcination has piezoelectric catalytic performance without polarization; in particular, it can be seen from the experimental results of Example 3, Comparative Example 3 and Comparative Example 4 that the piezoelectric catalytic performance of the barium titanate ceramic piezoelectric film is enhanced by utilizing the increased grain boundary density, and the enhancement effect is better than the enhancement of the piezoelectric catalytic performance brought about by the polarization treatment.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a barium titanate ceramic piezoelectric film, It is characterized in that The following steps are involved: Step S100, obtaining a barium titanate precursor solution, wherein the raw materials of the barium titanate precursor solution include a barium source and a titanium source, the mass percentage of the barium source in the raw materials is 20% to 25%, and the stoichiometric molar ratio of the titanium source and the barium source in the raw materials is 1:1; the raw materials of the barium titanate precursor solution also include a thickening crosslinking agent; the raw materials of the barium titanate precursor solution also include a solvent, and the solvent is any one of an acetic acid-ethanol-deionized water solvent system, an acetic acid-DMF-deionized water solvent system, and an acetic acid-DMF-acetylacetone system; Step S200, preparing a barium titanate precursor film from a barium titanate precursor solution by electrostatic spinning; Step S300, calcining the barium titanate precursor film to obtain a barium titanate ceramic piezoelectric film.

2. The preparation method according to claim 1, It is characterized in that The barium source is at least one of barium titanate, barium acetate, barium sulfate, barium nitrate, barium chloride, barium hydroxide and barium oxide.

3. The preparation method according to claim 1, It is characterized in that The titanium source is at least one of titanium dioxide colloid, titanium trichloride, titanium tetrachloride, titanyl sulfate, titanyl acetylacetonate, isopropyl titanate, tetrabutyl titanate and tetraethyl titanate.

4. The preparation method according to claim 1, It is characterized in that During the electrospinning process, the barium titanate precursor sol is electrospun onto a spinning template having a topological structure. The positive voltage for controlling electrospinning was +16 kV, and the negative voltage was -4 kV; and / or, the spinning temperature is controlled at 25±5°C and the humidity is controlled at 40%±5%; And / or, the spinning thickness is controlled to be 3 μm~10 μm.

5. The preparation method according to claim 1, It is characterized in that In the electrospinning process, the barium titanate precursor sol is electrospun onto a common receiver.

6. The preparation method according to any one of claims 1 to 3, It is characterized in that In step S300, the calcination temperature is controlled to be 650°C-900°C, and the calcination time is 8 hours.

7. The preparation method according to claim 6, It is characterized in that In step S300, during calcination, the temperature is increased to 650°C-900°C at a heating rate of 2°C / min and maintained in this temperature range for calcination for 8 hours, and then cooled to room temperature at a cooling rate of 5°C / min to obtain a barium titanate ceramic piezoelectric film.

8. A barium titanate ceramic piezoelectric film, It is characterized in that Prepared by the preparation method according to any one of claims 1 to 7.